2019
DOI: 10.1177/1942602x19831655
|View full text |Cite
|
Sign up to set email alerts
|

Advocating for Oral Health Through Fluoridation

Abstract: Eight school nurses attended the American Academy of Pediatrics’ Campaign for Dental Health meeting in March 2018, which focused on community water fluoridation programs. Because of aging infrastructure and antifluoridation community activists, some communities are considering stopping fluoridation programs. The benefits of water fluoridation have been demonstrated since the 1950s. School nurses can play a vital role in advocating for evidence-based fluoridation programs within their community. This article in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In England, water fluoridation has been established to decrease tooth caries by 44% in preschool children aged around five years [3,4]. Water and water-based drinks are the chief cause of systemic intake of fluoride; approximately 75% of dietary fluoride ingestion in the population is due to fluoridated water [5]. Several processes of fluoride intake are presented, which are in the form of topical fluoride or systemic fluoride.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In England, water fluoridation has been established to decrease tooth caries by 44% in preschool children aged around five years [3,4]. Water and water-based drinks are the chief cause of systemic intake of fluoride; approximately 75% of dietary fluoride ingestion in the population is due to fluoridated water [5]. Several processes of fluoride intake are presented, which are in the form of topical fluoride or systemic fluoride.…”
Section: Introductionmentioning
confidence: 99%
“…In the Kingdom of Saudi Arabia (KSA), tooth decay is an important public health issue, affecting the primary dentition of around 95%of kids aged 3-7 years, around 91% youngsters aged between 12 and 19 years, and 98% of adults aged between 30 and 45 years [3].Especially, in the eastern province of KSA, the overall frequency of dental caries among children aged between 6 and 9 years and10 and 12 years is 73% and 68%, respectively [3].Water fluoridation is considered as a cost-effective measure for caries-prevention in individuals of moderate to high caries risk. In addition, it has a strong safety profile, with the only side effect being a low risk of very mild fluorosis (~2%), which itself may not essentially be due to the exposure to increasing levels of fluoride alone [2,5,6].A study showed that 75% of public water supplied in the central province cities of Riyadh and Qassim has fluoride levels between 0 and 6 ppm [9].One more study performed in three cities of the western province of Saudi Arabia discovered varying fluoride levels, ranging from0.3 to 2.5 ppm, depending on the water supply source [3]. However, the US Department of Health and human services suggests that the optimal water fluoride level for humans with negligible risk is 0.7 ppm [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted in England, fluoridating water can lower tooth decay by 44% among preschoolers aged around five years old [15,16]. The most common source of systemic intake of fluoride is water, which is responsible for about 75 percent of people who consume fluoride in their diets [17]. Some countries are unaware of the significance of having an optimal fluoride level in their drinking water.…”
Section: Fluoride Health Impactsmentioning
confidence: 99%
“…Environmental fluoride is a natural process [1], and water and beverages are responsible for approximately 75% of the dietary fluoride intake [2]. The population consumes more bottled water than public water due to industrialization, accessibility, and concerns about water quality, safety, and practicability, even though there is a higher cost when compared to public water [3].…”
Section: Introductionmentioning
confidence: 99%